2021
DOI: 10.21203/rs.3.rs-1065719/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linking individual differences in human V1 to perception around the visual field

Abstract: A central question in neuroscience is how the organization of cortical maps relates to perception, for which human primary visual cortex (V1) is an ideal model system. V1 nonuniformly samples the retinal image, with greater cortical magnification (surface area per degree of visual field) at the fovea than periphery, and at the horizontal than vertical meridian. Moreover, the size and organization of V1 differs greatly across individuals. Here, we used fMRI and psychophysics in the same individuals to quantify … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…It is possible that individual variation in the distribution (as opposed to overall quantity) of retinal cell populations over eccentricity or polar angle may be reflected in the visual cortex. Indeed, recent work has shown that polar angle variation in group and individual measures of perception are related to variation in cortical magnification across area V1 (Benson et al, 2021; Himmelberg, et al, 2021; Kupers et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that individual variation in the distribution (as opposed to overall quantity) of retinal cell populations over eccentricity or polar angle may be reflected in the visual cortex. Indeed, recent work has shown that polar angle variation in group and individual measures of perception are related to variation in cortical magnification across area V1 (Benson et al, 2021; Himmelberg, et al, 2021; Kupers et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These individual differences are not explained by variation in whole brain size (Andrews et al, 1997;Benson et al, 2021). Moreover, some studies have found that individual differences in V1 size can be related to properties of visual perception (Duncan and Boynton, 2003;Schwarzkopf et al, 2011;Song et al, 2013Song et al, , 2015Genç et al, 2015;Bergmann et al, 2016;Himmelberg et al, 2021). Understanding what factors influence individual differences in V1 size is likely to clarify our understanding of how human visual processing and perception vary across people.…”
Section: Introductionmentioning
confidence: 99%